(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The paper aims to commemorate François Menant, who recently passed away, by presenting the studies he devoted to Lombardy, starting with his doctoral thesis on Campagnes lombardes du Moyen Age and ending with his most recent research.